High temperatures augment inhibition of parasites by a honey bee gut symbiont - Palmer-Young, Evan C.; Markowitz, Lindsey M.; Huang, Wei-Fone; Evans, Jay D. (Applied and environmental microbiology, 2023)
Temperature affects growth, metabolism, and interspecific interactions in microbial communities. Within animal hosts, gut bacterial symbionts can provide resistance to parasitic infections. Both infection and populations of symbionts can be shaped by the host body temperature. However, the effects of temperature on the antiparasitic activities of gut symbionts have seldom been explored. The Lactobacillus -rich gut microbiota of facultatively endothermic honey bees is subject to seasonal and ontogenetic changes in host temperature that could alter the effects of symbionts against parasites. We used cell cultures of a Lactobacillus symbiont and an important trypanosomatid gut parasite of honey bees to test the potential for temperature to shape parasite-symbiont interactions. We found that symbionts showed greater heat tolerance than parasites and chemically inhibited parasite growth via production of acids. Acceleration of symbiont growth and acid production at high temperatures resulted in progressively stronger antiparasitic effects across a temperature range typical of bee colonies. Consequently, the presence of symbionts reduced both the peak growth rate and heat tolerance of parasites. Substantial changes in parasite-symbiont interactions were evident over a temperature breadth that parallels changes in diverse animals exhibiting infection-related fevers and the amplitude of circadian temperature variation typical of endothermic birds and mammals, implying the frequent potential for temperature to alter symbiont-mediated resistance to parasites in endo- and ectothermic hosts. Results suggest that the endothermic behavior of honey bees could enhance the impacts of gut symbionts on parasites, implicating thermoregulation as a reinforcer of core symbioses and possibly microbiome-mediated antiparasitic defense. Two factors that shape the resistance of animals to infection are body temperature and gut microbiota. However, temperature can also alter interactions among microbes, raising the question of whether and how temperature changes the antiparasitic effects of gut microbiota. Honey bees are agriculturally important hosts of diverse parasites and infection-mitigating gut microbes. They can also socially regulate their body temperatures to an extent unusual for an insect. We show that high temperatures found in honey bee colonies augment the ability of a gut bacterial symbiont to inhibit the growth of a common bee parasite, reducing the parasite’s ability to grow at high temperatures. This suggests that fluctuations in colony and body temperatures across life stages and seasons could alter the protective value of bees’ gut microbiota against parasites, and that temperature-driven changes in gut microbiota could be an underappreciated mechanism by which temperature—including endothermy and fever—alters animal infection.